Review of X-ray detection systems - Urbański , Paweł; Grzebyk, Tomasz (Opto-Electronics Review, 2023)
The article presents an overview and a classification of X-ray detection methods. The main motivation for its preparation was the need to select a suitable and useful method for detecting signals from a currently developed miniature micro-electro-mechanical system (MEMS) X-ray source. The described methods were divided into passive and active ones, among which can be distinguished: chemical, luminescent, thermo-luminescent, gas ionization, semiconductor, and calorimetric methods. The advantages and drawbacks of each method were underlined, as well as their usefulness for the characterisation of the miniature MEMS X-ray source.